Seismic response evaluation of a five‐story buckling‐restrained braced frame using multi‐element pseudo‐dynamic hybrid simulations. (6th July 2021) - Mojiri, Saeid; Mortazavi, Pedram; Kwon, Oh‐Sung; Christopoulos, Constantin
Abstract: Nonlinear time history analysis relies on accurate modeling of the critical structural components and their complex interaction with the structure. Previous research indicates that calibration of numerical models can be affected by several factors, including the loading protocols. It is, therefore, critical to study previously developed and calibrated numerical models under more realistic loading histories, and determine whether the calibration process, loading protocols, and the numerical model themselves are adequate for achieving the desired level of accuracy. High fidelity benchmark system‐level experimental‐based simulation results could allow for a more holistic assessment of such questions. The University of Toronto Ten Element Hybrid Simulation Platform (UT10) was developed to produce such benchmark test results using hybrid simulations with multiple experimental elements subjected to realistic earthquake loads. This paper presents the first such experiment in the UT10 with multi‐element and single‐element experimental hybrid simulations on a five‐story steel structure with buckling‐restrained braces, representative of systems with a stable yielding hysteretic response. An adjustable yielding brace system was developed to capture the response of buckling‐restrained braces' yielding core. The implications of modeling choices, such as using commonly available models in BRBFs, are studied. The experimental results are then presented and compared with numerical results. The limitations of existing models are identified. Such experimental results can be used by subsequent studies to improve the calibration of numerical models and allow for the development of more robust models, while also justifying the need for new loading protocols that could be used in the calibration process.